LESCH-NYHAN SYNDROME – late diagnosis of rare disease: clinical case - Oleksii Khaniukov; Valerii Chornyi; Ihor Yevstihnieiev; Ihor Hutnik; Oleksandra Smolianova; Nataliia Romuz; Kateryna Esterkina; Kateryna Pervieieva (Journal of V. N. Karazin Kharkiv National University: Series Medicine, 2021)
Background. Lesch-Nyhan syndrome is inherent X-linked recessive genetic disorder with decreased activity of hypoxanthine-guanine phosphoribosyltransferase (HGPRT). The disease is characterized by presence of the classical triad: hyperuricemia, neurological and behavioral changes. In the article we present a clinical case of Lesch-Nyhan syndrome first diagnosed only at 16 years old despite the fact that the clinical clues were already found at the patient`s early age.